Violência doméstica contra as mulheres e as políticas no Brasil e em Portugal nos anos de 2010 a 2020: https://doi.org/10.53809/TS_ISS_2022_n.3_83-98 ("Temas Sociais" Journal, 2022)
The article inteds to discuss domestic violence against women in Portugal and Brazil, through the analysis of policies and strategies adopted to prevent and solve the problem. This theoretical discussion contributes to the elaboration of effective policies. This article presents the historical-political perspective of the issue, the construction of policies and the actions taken in the last decade. This study is supported by a qualitative documentary method, with a literature, legislation and official documents review. The results indicate that Portugal privilegies protection, prevention, support and prosecution actions. Brazil has a national policy that prioritizes actions to combat and confront domestic violence, assistance, access and guarantee of rights to the victims. In conclusion, the policies of both coutries should include victims of violence to plan strategies and actions, enabling a better dialogue, more autonomy and inclusion of the different groups of women affected by the problem.